2020
DOI: 10.1016/j.arth.2019.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Implant Survivorship and Modes of Failure in Simultaneous Concurrent Bilateral Total Knee Arthroplasty

Abstract: a b s t r a c tBackground: There is limited evidence describing long-term implant survivorship and modes of failure in simultaneous concurrent bilateral total knee arthroplasty (TKA). Methods: We performed a retrospective review of 266 consecutive patients (532 knees) who underwent simultaneous concurrent bilateral TKA. We reviewed medical records for preoperative characteristics, perioperative complications, and revision surgeries. The primary outcome was TKA survivorship. Secondary outcomes included indicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 35 publications
1
5
0
1
Order By: Relevance
“…Our study shows significantly lower rates of revision-free implant survival at 5 years in patients less than age 40 years (77.2%), 40 to 49 years (88.9%), and 50 to 59 years (91.7%) when compared with population aged 60 to 79 years (>95%). These implant-survival rates are markedly lower in the less than 40 years and 40 to 49 years groups compared to the general TKA population in the literature, which show 5-year implant survival greater than 96.5% [13,22,27,29,30]. Five-year implant-survival rates in patients above 60 years of age in our study are consistent with those previously reported.…”
Section: Discussionsupporting
confidence: 91%
“…Our study shows significantly lower rates of revision-free implant survival at 5 years in patients less than age 40 years (77.2%), 40 to 49 years (88.9%), and 50 to 59 years (91.7%) when compared with population aged 60 to 79 years (>95%). These implant-survival rates are markedly lower in the less than 40 years and 40 to 49 years groups compared to the general TKA population in the literature, which show 5-year implant survival greater than 96.5% [13,22,27,29,30]. Five-year implant-survival rates in patients above 60 years of age in our study are consistent with those previously reported.…”
Section: Discussionsupporting
confidence: 91%
“…Continued advancements in technology and improvement in surgical techniques have made TKA surgery a very successful operation [ 25 ]. However, approximately one-third of early TKA revisions are related to unbalanced soft tissue presenting as stiffness, instability, or early component loosening [ 8 , 26 31 ]. The ligament balancing "feeling" is affected by factors such as patient generalized laxity, degree of joint contracture, BMI, gender, the depth of anesthesia, surgical experience, and even the surgeon's favorite method of balancing(spacer blocks or ligament tensioners) [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Total knee arthroplasty (TKA) is considered to be an effective surgical treatment for knee osteoarthritis that can result in substantial improvements in knee function and patient quality of life [ 1 ]. However, the polymeric tibial insert is prone to wear due to the considerable loads placed upon it, which can lead to the generation of wear particles and subsequent loosening of the implant due to bone resorption [ 2 , 3 ]. Many methods have been used to improve the wear resistance in the previous reports [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%